Analisis ketersediaan tenaga kerja terampil dan tenaga kerja tidak terampil terhadap pertumbuhan ekonomi Provinsi di Sumatera - Dwi Nanda Putri, Indah; Achmad, Erni; Vyn Amzar, Yohanes (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2025)
This study aims to determine and analyze the development of skilled and unskilled labor in the Provinces of Sumatra and the Economic Growth of the Provinces of Sumatra. and to determine and analyze the influence of skilled and unskilled labor on the Economic Growth of the Provinces of Sumatra in 2019-2023. This study uses secondary data from BPS using quantitative descriptive methods. The analytical tool used is the panel data regression analysis method. The results of the study from 2019-2023 show that the Average Economic Growth in Sumatra is 2.85 percent. Skilled labor Education in Sumatra is 3.54 percent. Skilled labor training in Sumatra is 23.59 percent. Unskilled labor in Sumatra is 2.54 percent. While both partially and simultaneously the variable Skilled Labor Training has a significant positive effect on Economic Growth, and Unskilled Labor has a negative and significant effect on Economic Growth, while Skilled Labor education has a negative and insignificant effect on the Economic Growth of the Provinces of Sumatra.